A study on the identity formation of tea garden workers: stories curtained in the narrative of development - Tabassum, Syeda Sayka (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2019.